2019
DOI: 10.3389/fgene.2019.00548
|View full text |Cite
|
Sign up to set email alerts
|

A Review of African Americans’ Beliefs and Attitudes About Genomic Studies: Opportunities for Message Design

Abstract: Precision Medicine, the practice of targeting prevention and therapies according to an individual’s lifestyle, environment or genetics, holds promise to improve population health outcomes. Within precision medicine, pharmacogenomics (PGX) uses an individual’s genome to determine drug response and dosing to tailor therapy. Most PGX studies have been conducted in European populations, but African Americans have greater genetic variation when compared with most populations. Failure to include African Americans in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Scholars studying the impact of race and ethnicity on views about return of genetic results have suggested that lower interest among minority groups may reflect concerns about a lack of access to healthcare that would allow them to follow up on actionable results [15] and distrust in the clinical and/or research community [10,48]. Similar concerns may exist among our participants from racial and ethnic minorities, though they may be further compounded by participants' "othering" within their communities.…”
Section: Discussionmentioning
confidence: 93%
“…Scholars studying the impact of race and ethnicity on views about return of genetic results have suggested that lower interest among minority groups may reflect concerns about a lack of access to healthcare that would allow them to follow up on actionable results [15] and distrust in the clinical and/or research community [10,48]. Similar concerns may exist among our participants from racial and ethnic minorities, though they may be further compounded by participants' "othering" within their communities.…”
Section: Discussionmentioning
confidence: 93%
“…African American participants are notably underrepresented in genomics research. 1 There are numerous reasons for this inequity, including mistrust, lack of awareness and access, concerns about the use of samples, and a desire for personal or community benefits. 1 Many of these originate from a history and persistence of unjust clinical and research practices [2][3][4] and the resultant untrustworthiness of medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these seemingly positive implications, public willingness to participate in genetic testing to inform medical care and views about pharmacogenomics use in clinical settings varies across demographic groups 1 , 14 , 15 . African Americans, who are at greater risk for experiencing health disparities 16 , 17 have been largely underrepresented in pharmacogenomic studies 18 . Though less likely to be included and participate in pharmacogenomic implementation studies, African American, or Black, patients have focused more on the positive benefits of personalized medicine (e.g., fewer side effects and less trial and error prescribing) than White patients 19 .…”
Section: Introductionmentioning
confidence: 99%